A framwork for dealing with fundamental knowledge problems through social media - Harri Jalonen (The International Journal of Management Science and Information Technology (IJMSIT), 2014)
This paper argues that the value of social media in knowledge (KM) can be evaluated on the basis of how social media helps to overcome four generic knowledge problems - i.e. uncertainty, complexity, ambiguity and equivocality. Drawing upon the relevant KM and social media literature, the paper discusses the four knowledge problems surrounding the knowledge management and presents a framework for overcoming them through social media. A literature synthesis involving inductive interpretation of qualitative research was used. The paper shows how different knowledge problems can be approached through social media: i) uncertainty can be reduced by decent problem formulation and effective information acquisition, ii) complexity can be simplified by increasing knowledge process capacity and decomposing problems, iii) ambiguity can be dissipated by sensemaking, iv) equivocality can be encountered by creating trust and allowing polyphony of perceptions. The paper contributes to the KM research by providing theoretically founded framework which illustrates the relationship between social media and knowledge problems. The framework can be used not only for identifying and understanding epistemological differences between knowledge problems but also for developing social media guidelines for KM purposes. Social media means not only new possibilities but also new threats to organisations' KM practices. The paper establishes the association between social media and the management of fundamental knowledge problems not previously discussed.
Keywords: 650; social media; knowledge problems